Sociolinguistics and language education - Hornberger, Nancy H.; McKay, Sandra (New perspectives on language and education, 2010)
"This book, addressed to experienced and novice language educators, provides an up-to-date overview of sociolinguistics, reflecting changes in the global situation and the continuing evolution of the field and its relevance to language education around the world. Topics covered include nationalism and popular culture, style and identity, creole languages, critical language awareness, gender and ethnicity, multimodal literacies, classroom discourse, ideologies and power. Whether considering the role of English as an international language or innovative initiatives in Indigenous language revitalization, in every context of the world sociolinguistic perspectives highlight the fluid and flexible use of language in communities and classrooms and the importance of teacher practices that open up spaces of awareness and acceptance of - and access to - the widest possible communicative repertoires for students." ""To those of us who 'came of age' with McKay and Hornberger's Sociolinguistics and Language Teaching (1996), this newly edited volume is a gift - a gift that will enable us to share our fascination with the social, cultural, and political aspects of language teaching with, our student teachers, while updating our own knowledge of sociolinguistics."-Yasuko Kanno, CITE, Temple University, USA" ""Sociolinguistics and Language Education brings together the most authoritative voices in the field to explore the intersections of language and education in contexts around the world. The editors have done a superb job in creating a resource that is comprehensive in its articulation of the complexities of social interactions in a globalized world yet simultaneously accessible, lucid, engaging, and thought-provoking."-Jim Cummins, OISE, University of Toronto, Canada" "Nancy H. Hornberger is Professor of Education and Director of Educational Linguistics at the University of Pennsylvania, USA. Recent three-time Fulbright Senior Specialist, to Paraguay, New Zealand, and South Africa respectively, Hornberger teaches, lectures, and advises on multilingualism and education throughout the world and has authored or edited over two dozen books." "Sandra Lee McKay is Professor Emeritus of English at San Francisco State University. Her newest book is International English in its Sociolinguistic Contexts: Towards a Socially Sensitive Pedagogy (with Wendy Bokhorst-Heng, Routledge, 2008). Recipient of numerous Fulbright grants and academic specialist awards, she has worked extensively in international teacher education in Asia, Africa, South America and Europe."